Nonhumans as Stakeholders: a Literature Review - Shachat, Madeleine (2024)
In this thesis, the concept of nonhumans as stakeholders, and the argumentation for or against this conception in academic literature, is approached through a scoping literature review methodology. The scoping review methodology was employed particularly due to its suitability for analysing emerging topics, such as the one of nonhuman stakeholdership. The research questions guiding this thesis were designed investigate how nonhuman stakeholders are defined, discussed, and represented in academic literature, and to gather information on the dominant theoretical frameworks used to ground their inclusion or exclusion as stakeholders. The study identifies key themes and arguments for and against the inclusion of nonhumans as stakeholders, ultimately revealing a lack of consensus and a variety of perspectives within the literature. The findings show that while the discourse on nonhuman stakeholders has grown significantly, particularly within the last 3 years, the topic remains largely underdeveloped in some areas, with a major issue being a lack of consensus on which kind of nonhuman stakeholder should be considered in the literature. This research highlights that the overall conception of nonhuman stakeholdership is still emergent and contentious within academic literature. The findings are also divided into three distinct eras to highlight the evolution of thought from a niche focus on the environment to a broader consideration of various nonhuman entities. Based on the synthesis of recommendations and conceptions across 64 reports over 30 years, the research agenda emphasizes the need for interdisciplinary approaches to better integrate nonhuman perspectives into stakeholder theory and practice, with many scholars advocating for a paradigm shift in how organizations engage with the nonhuman world. By systematically synthesizing the findings from the selected literature, this study addresses an existing research gap in stakeholder theory and lays the groundwork for future research in multiple disciplines, though the findings indicate that this topic is particularly relevant for environmental management and sustainability.